Research and application of Rayleigh wave extraction method based on microtremors signal analysis - Du, Qingling; Pan, Yanhui; Xin, Youyang (Frontiers in Physics, 2023)
This study investigates the method and application of single-channel, three-component microtremor signal co-directional Rayleigh surface-wave extraction. The research focuses on filtering linear polarization waves using polarizability wave and phase-difference filtering, which were analyzed based on both simulated data and real microtremor signals. Additionally, the study examines the use of time-frequency analysis to analyze microtremor signals and identify Rayleigh wave propagation direction. The combination of these methods leads to a set of procedures for extracting high-SNR co-directional Rayleigh surface waves from microtremor signals, which was applied to the elliptical polarizability imaging method. Results indicate that the proposed data processing process effectively filters linear polarization waves and accurately determines the propagation direction of the Rayleigh wave, leading to significant improvement in the accuracy of elliptical polarizability exploration results. This provides a reference for obtaining high signal-to-noise ratio data in microtremor Rayleigh wave seismic exploration.